SQ 22536, an Adenylate-Cyclase Inhibitor, Prevents the Antiplatelet Effect of Dazoxiben, a Thromboxane-Synthetase Inhibitor - Bertelé, Vittorio; Falanga, Anna; Tomasiak, Marian; Cerletti, Chiara; Gaetano, Giovanni de (Thrombosis and Haemostasis, 1984)
This study shows that dazoxiben, a selective inhibitor of thromboxane A2-synthetase in human platelets, inhibited arachidonic acid-induced platelet aggregation in platelet-rich plasma samples from four out of 16 healthy volunteers. In these four “responder” samples, the anti-aggregating effect of dazoxiben was prevented by the compound SQ 22536, a 9-substituted adenine analogue, endowed with an inhibitory activity on adenylate-cyclase. The compound SQ 22536 also counteracted the antiaggregating effect of prostaglandin D2, a known activator of platelet adenylate-cyclase. When platelet thromboxane A2-syn- thetase was blocked by dazoxiben, a marked increase of prostaglandin D2 was concomitantly observed both in “responder” and “non responder” samples. The compound SQ 22536 blunted the increase in platelet cAMP caused by either dazoxiben and sodium arachidonate or prostaglandin D2. It is suggested that the antiaggregating effect of dazoxiben is mediated by newly synthesized prostaglandin D2. The latter acts by stimulating adenylate-cyclase and increasing cAMP levels. The compound SQ 22536 prevents both phenomena. In “non responder” samples some factors - still to be defined - might counteract similarly to the compound SQ 22536 the antiaggregating activity of PGD2.
Keywords: Thromboxane synthetase inhibitors; Adenylate cyclase inhibitors; Prostaglandin D2; Cyclic AMP